Remote Treatment of Panic Disorder: A Randomized Trial of Internet-Based Cognitive Behavior Therapy Supplemented With Telephone Calls - Carlbring, Per; Bohman, Susanna; Brunt, Sara; Buhrman, Monica; Westling, Bengt E.; Ekselius, Lisa; Andersson, Gerhard (The American journal of psychiatry, 2006)
Objective: This study evaluated a 10-week Internet-based bibliotherapy self-help program with short weekly telephone calls for people suffering from panic disorder with or without agoraphobia. Method: After the authors confirmed the diagnosis by administering the Structured Clinical Interview for DSM-IV by telephone, 60 participants were randomly assigned to either a wait-listed control group or a multimodal treatment package based on cognitive behavior therapy plus minimal therapist contact via e-mail. A 10-minute telephone call was made each week to support each participant. Total mean time spent on each participant during the 10 weeks was 3.9 hours. The participants were required to send in homework assignments before receiving the next treatment module. Results: Analyses were conducted on an intention-to-treat basis, which included all randomly assigned participants. From pretreatment to posttreatment, all treated participants improved significantly on all measured dimensions (bodily interpretations, maladaptive cognitions, avoidance, general anxiety and depression levels, and quality of life). Treatment gains on self-report measures were maintained at the 9-month follow-up. A blind telephone interview after the end of treatment revealed that 77% of the treated patients no longer fulfilled the criteria for panic disorder, whereas all of the wait-listed subjects still suffered from it. Conclusions: This study provides evidence to support the use of treatment distributed via the Internet with the addition of short weekly telephone calls to treat panic disorder. Replication should be made to compare self-help and telephone treatment based on cognitive behavior methods with nonspecific interventions.